DeepRank: a deep learning framework for data mining 3D protein-protein interfaces - Nicolas Renaud (Nature Portfolio, 2021)
The authors present DeepRank, a deep learning framework for the data mining of large sets of 3D protein-protein interfaces (PPI). They use DeepRank to address two challenges in structural biology: distinguishing biological versus crystallographic PPIs in crystal structures, and secondly the ranking of docking models.